ANALYSIS SISTEM PERKREDITAN BANK MANDIRI SYARIAH TERHADAP USAHA KECIL MENENGAH - DWI PRIANTO RAHARDJO, MOHAMAD Priyanto (Jurnal Akuntansi AKUNESA, 2013)
Bank are financial’s institution as the financial between debitor and bank. Morethan, institution which is the function to allow the payment. Bank to give afacilities are credit, which is credit has given of UKM. This research the purposeto know the credit at Bank Mandiri Syariah with to UKM and analyzing credit atBank Mandiri Syariah. In the research used study case at Bank Mandiri Syariah.The research’s purpose is of credit of system of against UKM.Keywords: Bank, Credit, Usaha Kecil Menengah (UKM), System of Credit.